Wsparcie rozwoju przedsiębiorczości i innowacyjności w regionie (na przykładzie województwa kujawsko-pomorskiego) - Ignasiak-Szulc, Aranka; Piotrowska-Trybull, Marzena (Support of Enterprise and Innovations in a Region (Based on Kujawsko-Pomorskie Voivodeship), 2006)
The article discusses the possibilities of local government and business environment institutions influence on enterprise and innovations in the region and presents results of the research on support of SME sector in kujawsko-pomorskie voivodeship. The article raises the following problems: barriers of development that enterprises meet, the support from different institutions given to enterprises (including support from local government), opinions on gained support and expectations of enterprises regarding support from local government and other institutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 426-435